Sarcoglycan Complex in Human Normal and Pathological Prostatic Tissue: An Immunohistochemical and RT‐PCR Study. Issue 2 (18th December 2013) - Cutroneo, Giuseppina; Bramanti, Placido; Favaloro, Angelo; Anastasi, Giuseppe; Trimarchi, Fabio; Di Mauro, Debora; Rinaldi, Carmela; Speciale, Francesco; Inferrera, Antonino; Santoro, Giuseppe; Salvatore, Arena; Patricolo, Mario; et al.
ABSTRACT The sarcoglycan complex is a trans‐membrane system playing a key role in mechano‐signaling the connection from the cytoskeleton to the extracellular matrix. While β‐, δ‐, and ε‐sarcoglycans are widely distributed, γ‐ and α‐sarcoglycans are expressed exclusively in skeletal and cardiac muscle. Insufficient data are available on the distribution of sarcoglycans in nonmuscular tissue. In the present study, we used immunohistochemical and RT‐PCR techniques to study the sarcoglycans also in normal human glandular tissue, a type of tissue never studied in relation to the sarcoglycan complex, with the aim of verifying the real wider distribution of this complex. To understand the role of sarcoglycans, we tested specimens collected from patients affected by benign prostatic hyperplasia and adenocarcinoma. For the first time, our results showed that all sarcoglycans are detectable in normal samples both in epithelial and in myoepithelial cells; in pathological prostate, sarcoglycans appeared severely reduced in number or were absent. These data demonstrated that all sarcoglycans have a wider distribution suggesting a new unknown role for these proteins. The decreased number of sarcoglycans, containing cadherin domain homologs in samples of prostate affected by hyperplasia, and the absence of proteins in prostate biopsies, in cases affected by adenocarcinoma, could be responsible for the loss of adhesion between epithelial cells, which in turn facilitates the progression of benign tumors and the invasive potential of malignant tumors. Anat Rec, 297:327–336, 2014. © 2013 Wiley Periodicals, Inc.